Urban filter interrogating public space in postapartheid Johannesburg through the reintroduction of water as a civic amenity - Stokes, Kegan (My University, 2019)
Urban filter is about public space in Johannesburg, and seeks to provide an approach to a new space in the city that addresses the interpreted apprehension felt towards sharing space in it, specifically by those who established themselves on the northern suburban periphery following the fall of apartheid. Inspired by the physical link between the city’s urban and northern suburban environments that exists as the Braamfontein Spruit, the role of water in Johannesburg and its history is investigated in this project. Water – valuable in a city in which it is becoming increasingly scarce – is placed into civic space in an attempt to mediate the fear of public space in the city. This manifests as the proposal for a new swimming pool at the source of the Braamfontein Spruit in Berea, Johannesburg. The pool forms part of a larger facility that harvests and treats urban rainwater for use in it, while the overall proposal more significantly seeks to initiate conversation between its users towards a city that is more progressive towards an integrated and sustainable future
A research report submitted in partial fulfillment of the Masters of Architecture degree at the University of the Witwatersrand, Johannesburg. February 2019